A novel PGAM5 inhibitor LFHP-1c protects blood-brain barrier integrity in ischemic stroke - Chenglong Gao; Yazhou Xu; Zhuangzhuang Liang; Yunjie Wang; Qinghong Shang; Shengbin Zhang; Cunfang Wang; Mingmin Ni; Dalei Wu; Zhangjian Huang; Tao Pang (Elsevier, 2021)
Blood-brain barrier (BBB) damage after ischemia significantly influences stroke outcome. Compound LFHP-1c was previously discovered with neuroprotective role in stroke model, but its mechanism of action on protection of BBB disruption after stroke remains unknown. Here, we show that LFHP-1c, as a direct PGAM5 inhibitor, prevented BBB disruption after transient middle cerebral artery occlusion (tMCAO) in rats. Mechanistically, LFHP-1c binding with endothelial PGAM5 not only inhibited the PGAM5 phosphatase activity, but also reduced the interaction of PGAM5 with NRF2, which facilitated nuclear translocation of NRF2 to prevent BBB disruption from ischemia. Furthermore, LFHP-1c administration by targeting PGAM5 shows a trend toward reduced infarct volume, brain edema and neurological deficits in nonhuman primate Macaca fascicularis model with tMCAO. Thus, our study identifies compound LFHP-1c as a firstly direct PGAM5 inhibitor showing amelioration of ischemia-induced BBB disruption in vitro and in vivo, and provides a potentially therapeutics for brain ischemic stroke.